Acute Onset Infantile Spinal Muscular Atrophy - J Gordon Millichap (Pediatric Neurology Briefs)
Two infants who were asymptomatic at birth and presented at 3 and 6 months of age with acute onset generalized muscle weakness and hypotonia following respiratory infection are reported from the Schneider’s Children Hospital, New Hyde Park, NY.